Green Composites Sustainable Raw Materials - Muthu, Subramanian Senthilkannan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book highlights the production of green composites from various sustainable raw materials. We now live in an environmentally conscious era, in which sustainable raw materials (renewable, biodegradable, recycled), sustainable processing sequences, the production of recyclable and biodegradable products, and avoiding the depletion of renewable resources are key considerations with regarding to producing any product. The textile sector is no exception. Accordingly, this book addresses these aspects in connection with textiles, and discusses how they can be actively practiced.
Production of Green Composites from Various Sustainable Raw Materials -- Production of Sustainable Green Concrete Composites Comprising Industrial Waste Carpet Fibres -- Environmentally Benign and Sustainable Green Composites: Current Developments and Challenges.
Keywords: Manufactures; Ceramic materials; Sustainability; Industrial Management; Environmental engineering; Biotechnology; Bioremediation; Agriculture -- Economic aspects; Machines, Tools, Processes; Ceramics; Sustainability; Industrial Management; Environmental Engineering/Biotechnology.; Agricultural Economics